Progressive Muslim Intellectual as The Basic Concepts of New Paradigm on Integration Islam and Science Education - Dartim Ibnu Rushd; Mohamad Ali (J-PAI: Jurnal Pendidikan Agama Islam, 2025)
The background of this research is that there is still a lack of references on the integration of knowledge or "Islamic Intellectualism" concepts, especially those closely related to the ideals of progressive thought. This research is qualitative. All data obtained refers to written data sources. The sources include books, manuscripts, articles, and relevant documents, as well as research results and the results of interviews and field observations. The research was conducted with a historical-empirical approach. Furthermore, the data were analyzed using a qualitative analytical approach. Specifically looking for correlation, coherence, and relevance to draw conclusions. The research shows that the progressive intellectual character as a paradigm for understanding the integration of science and Islam can be framed in several categories. The category of Progressive Muslim Intellectual characters as the basis of a new paradigm on Integration Islam and Science Education includes: (1) Sufistic-modern A.R. Fakhruddin, (2) Purification-Dynamization from Tajdid Concept, (3) Inclusive-Tolerant Amin Abdullah, (4) Progressive-Modern Kiyai Dahlan, (5) (Liberation-Responsibility Mohamad Djazman). Furthermore, the profile’s implementation can be conducted in various scientific and religious practices. Such as literacy studies and scientific discussions, both religious and scientific book sources. Including its application in the environment in various activities that can be categorized in the scope of religiosity, intellectuality, and humanity.